Landscape design principles - Clokey, Jora; Stoltz, Ron; San Luis Video Publishing (Los Osos, California : San Luis Video Publishing, 2004)
Learn how to incorporate plants, topography and hardscape features with the baisc artistic principles of form, line, texture and color, plus much more. With clear terms and explanations, we will learn how to design landscapes which are appropriate, novel and well built
Title from title screen
DVD format
Keywords: Landscape design; Landscape architecture